1970
DOI: 10.1530/jrf.0.0230393
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in Female Wild Guinea-Pigs

Abstract: The breeding characteristics of three species of wild guineapig (F. Caviidae) are reported. Cavia aperea, Galea musteloides and Microcavia australis were studied in Argentina in the field and in outdoor pens, and laboratory colonies of the two former species were also established in England. Pens of domestic guinea-pigs (Cavia porcellus) and of C. aperea \m=x\C. porcellus hybrids were maintained in Argentina for comparisons with C. aperea. C. aperea and G. musteloides gave birth in every month but there was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
15

Year Published

1975
1975
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 7 publications
2
42
0
15
Order By: Relevance
“…In" fact, guineapigs appear to exhibit a strong herd of family behaviour which is supported by observations of feral animals (Rood, 1970;Rood, 1972). This need for close group association contrasts sharply with the aggressive territorial behaviour of other rodents.…”
Section: Introductionmentioning
confidence: 60%
“…In" fact, guineapigs appear to exhibit a strong herd of family behaviour which is supported by observations of feral animals (Rood, 1970;Rood, 1972). This need for close group association contrasts sharply with the aggressive territorial behaviour of other rodents.…”
Section: Introductionmentioning
confidence: 60%
“…This membrane has been recorded in all hystricomorphs studied so far, except the coypu, Myocastor coypus (Weir, 1974). Rowlands & Weir (1977) regarded the perforation of this membrane as an 'external indicator of ovulation' and synchronization of perforation with regular surges of oestradiol-17ß concentrations in peripheral blood in the porcupine confirmed this (Rood & Weir, 1970;Weir, 1973a) and behavioural as well as pheromonal mechanisms may be involved in initiating cyclic ovarian activity in porcupines. Gestation lengths reported here (93-94 days) were accurately measured since they were based on calculations of the interval between observed matings and normal parturition with pregnant females isolated from fertile males during that interval.…”
Section: Lactationmentioning
confidence: 79%
“…Lactation anoestrus is not unusual for hystricomorph rodents and occurs in the chinchilla (Weir, 1973b), the wild guinea-pig (Rood & Weir, 1970), green acouchi (Weir, 1971a) and plains viscacha (Weir, 1971b).…”
Section: Lactationmentioning
confidence: 99%
“…Subsequent studies on the reproduction of this species have been almost exclusively directed towards the female and have resulted in the establishment of the length of the oestrous cycle, gestation period and the effects of season on breeding performance (Rood & Weir, 1970). Weir (1971) also found that the occurrence of the oestrous cycle could be influenced by the presence of a male.…”
Section: Discussionmentioning
confidence: 99%